Diseño de un prototipo de sistema de arado mecánico (Tipo Cincel) para terrenos franco-arenosos en la finca Las Flores de Villavieja (Huila) (2022)
Mechanical soil preparation systems based on the use of plow systems constitute a technological base to improve the dynamics of germinal development of a plant and production costs, however, currently the preparation work demands high daily wages and therefore additional costs in the process; to solve these problems, a proposal for a "prototype of a mechanical plow system (chisel type) for sandy loam soils in the Las Flores de Villavieja (Huila) farm was developed. The research is exploratory-descriptive and phased. The evaluation of prototypes is based on a morphological matrix with two design alternatives, which focused on increasing the number of plow lines to increase the furrowing of the soil for subsequent planting, according to the above, the prototype plow system composed of 11 lines with a star chisel configuration is the most suitable and convenient option for the farm; when analyzing the chisel using the Von Mises method, it was concluded that the maximum effort supported by it is 83.86 Mpa, which generates a maximum displacement of 0.2282 mm with a design factor of 0. 2282 mm with a design factor of 3.74; the study concludes that in order to achieve a highly efficient design, the client's requirements must be considered conceptually.